Phytotherapy: an introduction to its history, use and application - T.S. Ferreira; C.Z. Moreira; N. Z. Cária; G. Victoriano; W.F. SILVA Jr; J.C. Magalhães (Universidade Estadual Paulista, 2014)
There has been a great advance in the pharmacognosy field, which has increased the use of medicinal plants by health professionals and practitioners of folk medicine. This systematic review explored the history and the present day application of phytotherapeutic medicines. We searched the databases Cochrane Library, Embase, Lilacs, PubMed, Scielo and a specialized bibliography. We concluded that there are many therapeutic potentialities in the use of phytotherapeutic medicines and medicinal plants. We also concluded that despite the increasing number of publications in the field each year, there is still a lack of reviews and meta-analyses that could promote a better integration of the knowledge produced. In addition, research about pharmacological interactions and multidisciplinary studies may promote a quicker and safer process from the workbench up to the clinical trials.